Histamine metabolism of the guinea-pig gastric mucosa. - Bergmark, J (1976)
1. The mobilization of gastric mucosal histamine as reflected by changes in formation and content has been studied in guinea-pigs on feeding and after injections of pentagastrin or 2-deoxy-D-glucose. 2. Re-feeding fasting guinea-pigs as well as injections of pentagastrin or 2-deoxy-D-glucose raised the rate of mucosal histamine formation; pentagastrin induced a fourfold rise. 3. Some properties of the enzyme catalysing the formation of histamine were examined. The results indicated that this enzyme is histidine decarboxylase, L-histidine carboxy-lyase, E.C. 4.1.1. 22. 4. The enzyme imidazole-N-methyl transferase, E.C. 2.1.1.8, which carries out methylation of the imidazole ring to yield 1-methyl-4-(beta-aminoethyl)imidazole (methylhistamine), was found in high amounts in the mucosa. The enzyme did not change upon stimulation of the mucosa. 5. The metabolism of histamine within the gastric mucosa is discussed in relationship to a suggested role of the amine in exciting acid secretion.